2006
DOI: 10.2139/ssrn.904355
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Environment Using the Life-Satisfaction Approach

Abstract: This paper presents a comprehensive theoretical and methodological framework clarifying the relationship between non-market environmental valuation techniques, in particular hedonic and life-satisfaction methods. The paper shows how life-satisfaction scores can be used to test correctly the equilibrium condition in location markets required by the hedonic approach and that in the absence of equilibrium, the life-satisfaction approach is still a theoretically valid valuation technique. Valuation using the life-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Furthermore, while happiness studies have recently been used to estimate the value of public goods and bads, including price inflation (Di Tella et al, 2001), state cigarette taxes (Gruber and Mullainathan, 2005), airport noise (van Praag and Baarsma, 2005), inequality (Alesina et al, 2004), terrorism (Frey et al, 2009), and even air pollution (Welsch, 2007;Ferreira et al, 2006;Luechinger, 2009), all of this previous work relies on annual average values of these public goods across regions or countries. If the public goods are endogenously determined by regional characteristics also associated with happiness, or if people become habituated to levels of public goods, these studies using annual regional differences in public goods will yield biased estimates of willingness to pay.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while happiness studies have recently been used to estimate the value of public goods and bads, including price inflation (Di Tella et al, 2001), state cigarette taxes (Gruber and Mullainathan, 2005), airport noise (van Praag and Baarsma, 2005), inequality (Alesina et al, 2004), terrorism (Frey et al, 2009), and even air pollution (Welsch, 2007;Ferreira et al, 2006;Luechinger, 2009), all of this previous work relies on annual average values of these public goods across regions or countries. If the public goods are endogenously determined by regional characteristics also associated with happiness, or if people become habituated to levels of public goods, these studies using annual regional differences in public goods will yield biased estimates of willingness to pay.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that climatic conditions affect life satisfaction at the aggregated country level [31] and also at the individual level [32,33]. Similarly, air pollution has been found to affect life satisfaction at the aggregated country level [34,35,36], as well as the individual level [37,38]; one study known to us has also found an effect of perceived air pollution on life satisfaction [30]. It is important to note that factors of life satisfaction may interact in a way that either attenuates or amplifies the direct effects of those factors on life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are closer to those found in the studies by Levinson (), who used panel data and the studies by MacKerron and Mourato () and Ferreira et al . ().…”
Section: Empirical Results and Discussionmentioning
confidence: 97%
“…Second, the interest of population as it has been discussed is the non‐movers sample, which has been considered only in the study by Luechinger (). Third, some of these studies assign the air pollution based on large geographical areas (Welsch, ) or they employ cross‐sectional data (Ferreira et al ., ; MacKerron and Mourato, ). In addition, MacKerron and Mourato () explored only London, which can be highly polluted due the high traffic volume.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation